Collective behaviour : Jackdaws vote to leave with their voice - Farine, Damien R. (My University, 2022)
Making a decision as a group requires not only choosing where to go but also when to go. A new study provides experimental evidence that, in jackdaws, vocalisations facilitate synchronous early morning departures from communal roosts.
Keywords: 570